(Ns^ETNYE BULEWY ALGEBRY (B/s - (NgON^AROW(B, (NsERGEJ sEWOSTXQNOWI^s; (NeR[OW(B, (N`(B.(Nl(B.s ((NnOWOSIBIRSK (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 171-174 (82 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT MATEMATIKIs
Keywords: (NaLGEBRA LOGIKIs